2017
DOI: 10.31223/osf.io/wcxny
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising Drainage Multiphase Flow in Heterogeneous Sandstones

Abstract: In this work, we analyse the characterisation of drainage multiphase flow properties on heterogeneous rock cores using a rich experimental dataset and mm-m scale numerical simulations. Along with routine multiphase flow properties, 3D sub-metre scale capillary pressure heterogeneity is characterised by combining experimental observations and numerical calibration, resulting in a 3D numerical model of the rock core. The uniqueness and predictive capability of the numerical models are demonstrated by accurately … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…First, traditional approaches are impacted by experimental artifacts, such as the capillary end effects, as described in detail in Figure 3. Another advantage of using PNM to characterize capillary heterogeneity is that measurements are not influenced by viscous forces that are typically ignored with assumptions of capillary equilibrium across the system (Krause et al, 2013;Pini & Benson, 2013Jackson, Agada, et al, 2018;Hejazi et al, 2019). Finally, approaches for quantifying capillary heterogeneity rely on J-Leverett scaling (Leverett, 1940;Krause et al, 2013;Pini & Benson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First, traditional approaches are impacted by experimental artifacts, such as the capillary end effects, as described in detail in Figure 3. Another advantage of using PNM to characterize capillary heterogeneity is that measurements are not influenced by viscous forces that are typically ignored with assumptions of capillary equilibrium across the system (Krause et al, 2013;Pini & Benson, 2013Jackson, Agada, et al, 2018;Hejazi et al, 2019). Finally, approaches for quantifying capillary heterogeneity rely on J-Leverett scaling (Leverett, 1940;Krause et al, 2013;Pini & Benson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work found that permeability heterogeneity is not the dominant fluid distribution mechanism at lower flow rates (Jackson et al, 2018). Furthermore, Leverett-J function scaling is invalid for rocks with a multi-modal porosity (Sarwaruddin et al, 2001).…”
Section: Accepted Articlementioning
confidence: 97%
“…It is well known that laboratory relative permeability measurements are strongly influenced by permeability heterogeneity within cores that arises from sedimentary structures like crossbedding in sandstones or shell fragments in carbonates (Corey & Rathjens, 1956;Huppler, 1970;Kortekaas, 1985;Hove et al, 1990;Hamon & Roy, 2000;Dawe et al, 1992;Chang & Yortsos, 1992). The impact of porosity and capillary heterogeneity is less well understood although recent research indicates that it is one of the leading causes of anisotropy and flow rate dependency in observed relative permeability and thus can have a significant impact on upscaled properties (Krishnamurthy et al, 2017(Krishnamurthy et al, , 2019Jackson et al, 2018;Boon & Benson, 2021;Ershadnia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations